Beyond Genetic Discrimination: Emerging Challenges in the Age of Artificial Intelligence - Li Li Zhenkang (Issues in Law & Medicine, 2026)
With the deep integration of artificial intelligence and biotechnology, the paradigm of genetic discrimination is undergoing a fundamental transformation. Rather than relying on specific genetic markers, AI systems may infer individuals’ underlying biological risks through proxy data. This emerging form of discrimination, conceptualized in this article as “Algorithmic Proxy Genetic Discrimination” (APGD), is predictive, opaque, and structural. However, China’s existing Personal Information Protection Law and fragmented antidiscrimination framework remain insufficient to address this problem. In addition, APGD raises profound ethical and social challenges. To mitigate these risks, this article proposes a tiered regulatory approach: (1) controlling the misuse of proxy variables at the data input stage; (2) strengthening transparency and auditing in algorithmic decision-making; and (3) establishing an outcome-oriented mechanism for anti-discrimination liability and rights protection.